3D bioprintable methacrylated carrageenan/sodium alginate dual network hydrogel for vascular tissue engineering scaffolding. Issue 7 (3rd May 2023) - Zhou, Anduo; Hu, Yasong; Chen, Chongshuai; Mao, Heyi; Wang, Lei; Zhang, Shanfeng; Huang, Xia
Abstract: 3D printing technology has significant advantages in the processing field of vascular tissue engineering. We have developed KCMA/SA hydrogels based on methacrylated carrageenan (KCMA) and sodium alginate (SA), which have low viscosity and shear thinning properties and can be used for 3D printing. The physicochemical double cross-linked network structure leads to good mechanical properties. The composite hydrogels maintain the liquid crystallinity of KC, which causes the HUVECs to align. The KCMA/SA gel filaments printed by the 3D extrusion printing system formed a connected microstructure. These characteristics all indicate the potential of KCMA/SAs in the field of tubular tissue regeneration. Graphical Abstract: UF0001